Uji Efektivitas Eksrak Kulit Pisang Goroho (Musa Acuminate L.) Terhadap Penurunan Kadar Glukosa Darah pada Tikus Putih Jantan Galur Wistar yang diinduksi Sukrosa - Syamsuddin, Sri Murti Sari; Edy, Hosea Jaya; Supriati, Hamidah Sri (PHARMACON, 2013)
ABSTRACT The objectives of this research were to study the effect of Goroho banana (Musa Acuminate L.) peel extract on the decreasing of blood glucose contentÂ  of white male wistar induced with sucrose. This research using Randomized Controlled Group Design .The subjects in these research were 15 mices which divided into 3 groups, namely negative control (aquadest),Â  treatments groupusing Goroho banana peel extract 0,03 g/KgBB, and positive control using metformin 45 mg/KgBB. Data were obtained from fasting blood glucose examination, 30 minutes after induced with sucrose, and at 15, 30, 60, and 120 minutes treatment. Data analyzed statistically using ANOVA (Analysis Of Variant), the results extract goroho banan peel provide an effect on blood glucose content. LSD (Least Significant Different) domonstrate distinct difference, significant effect between negative group with treatment, negative group with positive group, but did not show differences between treatment group with positive group. Is Goroho banana peel extract exhibit activity to decrease blood glucose content of white male wistar induced with sucrose. Keywords: Musa acuminate L. goroho banana peel, blood glucose content, sucrose